Myositis, Ganglioneuritis, and Myocarditis with Distinct Perifascicular Muscle Atrophy in a 2-Year-Old Male Boxer - Rossman, Paul M.; Thomovsky, Stephanie A.; Schafbuch, Ryan M.; Guo, Ling T.; Shelton, G. D. (Frontiers in Veterinary Science, 2018)
A 2-year-old male, intact Boxer was referred for chronic diarrhea, hyporexia, labored breathing, weakness and elevated creatine kinase and alanine aminotransferase activities. Initial examination and diagnostics revealed a peripheral nervous system neurolocalization, atrial premature complexes and generalized megaesophagus. Progressive worsening of the dog’s condition was noted after thirty-six hours; the dog developed aspiration pneumonia, was febrile and oxygen dependent. The owners elected humane euthanasia. Immediately post mortem biopsies of the left cranial tibial and triceps muscles and the left peroneal nerve were obtained. Post mortem histology revealed concurrent myositis, myocarditis, endocarditis, and ganglioneuritis. Mixed mononuclear cell infiltrations and a distinct perifascicular pattern of muscle fiber atrophy was present in the both muscles. This is a novel case of diffuse inflammatory myopathy with a distinct perifascicular pattern of atrophy in addition to endocarditis, myocarditis and epicarditis.